Analysis of Fire Risk Associated with Photovoltaic Power Generation System - Guomin Zhao; Min Li; Lv Jian; Zhicheng He; Jin Shuang; Sun Yuping; Qingsong Zhang; Liu Zhongxian (Advances in Civil Engineering)
Because of increasing energy consumption and severe air pollution in China, solar photovoltaic power generation plants are being deployed rapidly. Owing to various factors such as technology, construction, and imperfection of construction standards, solar photovoltaic systems have certain fire risks. This paper focuses on the fire risks of building-integrated solar photovoltaic buildings, as well as temperature and heat flow density near a photovoltaic system in a fire. Based on FDS simulation results, the influence of different building fires on photovoltaic systems is analysed. It is found that the influence of fire on photovoltaic systems installed on a building with a flat roof is stronger than that on a system installed on a building with a sloping roof; the influence of fire on a photovoltaic system installed on a building with external wall thermal insulation is stronger than that on a system installed on a building without such insulation; and in the presence of a skylight, a photovoltaic system installed on a building with a sloping roof is more dangerous.